The species-energy theory: A role for energy variability - Carrara, Rodolfo (2010)
Species-energy theory posits that energy availability regulates population sizes, extinction rates and ultimately species richness. This theory has focused mostly on total energy as a measure of energy availability. However, because energy variation can also influence population sizes and extinction rates, species-energy theory should arguably consider simultaneously both total energy and its variation. Using data on species richness of land birds and mammals, we compared the fit of three species-energy models including total energy, energy variation or both combined. We show that the combination of total energy and energy variation has greater predictive power than any of them considered separately. We also evaluate three crucial assumptions of this modified species-energy theory and show that they are supported by available data. These results illuminate the current debate on climate change, given that both average conditions and variability of climatic conditions are likely to change in the future.